PTH-353 Surgeon specific outcome data in colorectal cancer surgery - the patient perspective. (22nd June 2015) - Maclean, WAH; Park, S; Knight, JS
Abstract : Introduction: NHS England requires trusts to report individual outcomes in ten clinical specialties. In September 2013, the Association of Coloproctology of Great Britain and Ireland (ACPGBI) published individual surgeon and hospital outcomes detailing 90-day mortality rates after elective resection for bowel cancer. This data is available to view online. Our aims were to investigate patients' awareness and perspective of surgeon specific outcome data and to find out what was important to them about their upcoming operation. Method: Over a 6 month period, all consecutive patients attending preoperative assessment prior to resection for colorectal cancer at a teaching hospital were asked to complete the survey. Results: Of the 67 patients asked to complete the survey 66 (98.5%) responded. 13 of 66 (20%) patients stated they were aware of the surgeon specific outcome data and of those, 6 said they would know how to find it. 52 (79%) patients said the surgeon was more important than the hospital, 9 stated the hospital and 5 were undecided. When asked about other factors, 41 (67%) stated the reputation of the surgeon was the most important. Only 2 patients chose surgeon specific mortality rate, 18 said the number of times the operation had been performed by the surgeon in the preceding year and 5 did not answer the question. Conclusion: Most patients undergoing surgery for bowel cancer are unaware of the published outcome data for their surgeon. Of those that are aware less than half would know how to find it. However the overwhelming most important factor for the patient is the perceived reputation of the surgeon. Disclosure of interest: None Declared.